Oligo-Carrageenans Stimulate Growth by Enhancing Photosynthesis, Basal Metabolism, and Cell Cycle in Tobacco Plants (Var. Burley) - Moenne-Munoz, A; Gonzalez-Figueroa, A (2012)
Leaves of tobacco plants var. Burley were sprayed with water (control) or with oligo-carrageenans kappa2 (K), lambda (L), and iota (I) at 1 mg ml -1, once a week, four times in total, and cultivated for 4 months without treatment. Plants treated with K, L, and I showed an increase in leaf biomass of 1. 9, 1. 8, and 2. 5 times, respectively, despite that cellular size was similar in control and treated plants. In addition, net photosynthesis, efficiency of photosystem II and the level of chlorophyll a and b increased in plants treated with oligo-carrageenans. Moreover, the activity of ribulose 1,5-biphosphate carboxylase/oxygenase (rubisco) increased in treated plants, mainly with oligo-carrageenan I, whereas its content did not change compared to control plants. The activity of several NAD(P)H-synthesizing enzymes involved in basal metabolism increased in treated plants, mainly with oligo-carrageenan I. Furthermore, the relative level of transcripts encoding the cell cycle regulatory cyclins A and D and CDKs A and B increased in treated plants, mainly with oligo-carrageenan I. In addition, the amount of ascorbate (ASC) and the activity of ascorbate peroxidase (AP) increased in treated plants, mainly with oligo-carrageenan I, whereas the level of glutathione remained unchanged. Interestingly, the increases in total ascorbate and AP activity linearly correlated with the increase in leaf biomass. Thus, oligo-carrageenans enhanced photosynthesis, basal metabolism, and cell cycle as well as ASC levels and AP activity which may explain, at least in part, the stimulation of plant growth. © 2011 Springer Science+Business Media, LLC.